Nanopaper as an Optical Sensing Platform - Morales-Narváez, Eden; Golmohammadi, Hamed; Naghdi, Tina; Yousefi, Hossein; Kostiv, Uliana; Horák, Daniel; Pourreza, Nahid; Merkoçi, Arben (ACS nano, 2015)
Bacterial cellulose nanopaper (BC) is a multifunctional material known for numerous desirable properties: sustainability, biocompatibility, biodegradability, optical transparency, thermal properties, flexibility, high mechanical strength, hydrophilicity, high porosity, broad chemical-modification capabilities and high surface area. Herein, we report various nanopaper-based optical sensing platforms and describe how they can be tuned, using nanomaterials, to exhibit plasmonic or photoluminescent properties that can be exploited for sensing applications. We also describe several nanopaper configurations, including cuvettes, plates and spots that we printed or punched on BC. The platforms include a colorimetric-based sensor based on nanopaper containing embedded silver and gold nanoparticles; a photoluminescent-based sensor, comprising CdSe@ZnS quantum dots conjugated to nanopaper; and a potential up-conversion sensing platform constructed from nanopaper functionalized with NaYF4:Yb(3+)@Er(3+)&SiO2 nanoparticles. We have explored modulation of the plasmonic or photoluminescent properties of these platforms using various model biologically relevant analytes. Moreover, we prove that BC is and advantageous preconcentration platform that facilitates the analysis of small volumes of optically active materials (∼4 μL). We are confident that these platforms will pave the way to optical (bio)sensors or theranostic devices that are simple, transparent, flexible, disposable, lightweight, miniaturized and perhaps wearable.
Keywords: nanocellulose; optical sensors; Paper; optické prostředky; Biosensing Techniques; biosensing; celulosa; Optical Phenomena; absorpce radiace; photoluminescent devices; biosenzitivní techniky; kovové nanočástice; Absorption, Radiation; papír; optické jevy; Cellulose; composite; Quantum Dots; plasmonic devices; Optical Devices; kvantové tečky; Metal Nanoparticles